INTERSEKSI KONSEP PENDIDIKAN ABAD 21 DENGAN KURIKULUM MERDEKA PADA PENDIDIKAN DASAR - Jesica Dwi Rahmayanti; Alvina Nanda Setiaputri; Nur Laili; Zudan Rosyidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to describe the relationship between 21st century education and the independent curriculum in basic education. This research uses a Systematic Literature Review (SLR) approach to summarize and identify gaps that need to be filled from previous research, thereby producing unified literature on the concept of 21st century education and an independent curriculum. The literature used includes articles published in 2018-2023. These articles were selected based on title, abstract and keywords, so that 11 relevant journal articles were selected to be studied in this research. This research was carried out through three systematic stages consisting of, planning stage, conduction stage & reporting stage. The research results show that 21st century education directs students to play an active role in the learning process, mastering 21st century skills such as critical thinking, creative, collaborative, communicative, and mastering technology. Changes in education in the 21st century lead to improved quality of education, a better society, and a generation that is more adaptable. Providing education in the 21st century is an alternative for improving the quality of education, growing a generation that is more competitive and adaptable. The independent curriculum is here to provide new breakthroughs in the field of education, such as an active learning approach, application of contextual methods in learning, use of technology to increase literacy, and elaboration of metacognitive skills in students. The transformation of the independent curriculum is nothing but the spearhead of education in facing current developments and facilitating students to be able to develop various skills that must be achieved in the 21st century era.